Stressed-deformed state of the system «main pipeline – soil» in the karst sections (on the example of the section of the main gas pipeline «Power of Siberia», «Chayanda – Lensk») - Ezhkova, A. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
Currently, modern gas pipeline systems are increasingly demanding in terms of reliability, durability, industrial and environmental safety. Gas pipeline routes are located in poorly established regions where there are no long-term observations of hazardous natural processes. Currently, karst is the most latently occurring and difficult to predict hazardous engineering and geological process. In case of karst process along the pipeline route, additional load may be applied. In this regard, the analysis of the stress-strain state of the trunk gas pipeline-soil system is the most important task for determining the quantitative characteristics of stresses that can cause the development of emergency. The article considers the section currently built, the main gas pipeline "Power of Siberia," "Chayanda - Lensk." Carbonate formations of Cambrian age are widespread within the considered territory, there are manifestations of surface and underground forms of karst. In this regard, it is possible to activate the process during the operation stage, while during the design these geotechnical features may not have caused concerns. In this work, stress-strain analysis was carried out in case of joint deformation of the pipeline and soil under the influence of a possible load - karst dip. Proposals on the use of the obtained results at the operation stage are given.